Alpha- and beta-adrenergic receptors in the horse ureter (Revista Española de Fisiología, 1987)
The presence of both alpha and beta adrenergic receptors in the caudal third ureter of the horse were studied in vitro under isometric conditions using adrenergic agonist and antagonist drugs.Isoprenaline and the beta 2- stimulating agent, salbutamol, elicited relaxation of the ureter smooth muscle strips.The responses were not affected by the beta 1- blocking agent, practolol, but were totally abolished by propranolol and the beta 2- blocking agent, butoxamine.The stimulation of alpha-adrenergic receptors with noradrenaline and phenylephrine evoked a contractile effect which was totally inhibited by phenoxybenzamine and the alpha 1- blocking agent, prazosin.It is concluded that in the horse ureter the alpha receptors are dominant and belong to alpha 1 subtype while the beta receptors are recessive and belong to beta 2- adrenoceptor subtype.